(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The present work is an attempt to make comparative analysis of advertisements campaigns of Coke and Pepsi in terms of copy, positioning and punch line and their cognitive impact on the consumer’s preference, recall and purchase behavior. Comparative analyses of two advertisements campaign each of Coke and Pepsi was made by critically evaluating their copy, positioning strategy and punch line. Cognitive impact of advertisements was measured by analyzing the unaided brand recall ability, aided recall ability w.r.t to model, punch line and colour, factors influencing choice of a brand, impact of advertisement on purchase behavior and consumer preference for a brand. For the fulfillment of first objective, the ad campaigns were selected by conducted a survey in order to know the most popular ads. For consumer survey or second objective the population included all the consumers of soft drinks who were exposed to T.V advertisements in purposively selected Karnal City. The convenience sampling technique was followed in such a way that equal numbers of male and female respondents were selected and almost equal representation is provided to two different age groups. The information collected from respondents by means of a structured and non-disguised questionnaire was analyzed by taking percentage and mean scores.